2019
DOI: 10.36505/exling-2017/08/0004/000306
|View full text |Cite
|
Sign up to set email alerts
|

Loanwords stress and intonation in Algerian Arabic

Abstract: This paper deals with stress and intonation patterns of loanwords in Algerian Arabic and in particular in Algiers and Oran dialects. It shows that speakers always transferred the stress pattern of Algerian Arabic in borrowed words: the final syllable is stressed if it is the only heavy syllable in the word or if it is superheavy, otherwise stress is on the penultimate syllable. Intonation patterns are also transferred to loanwords in focus and polar questions. Focus is characterized in the Algiers dialect by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As far as the Algerian context is concerned, reviewing the literature revealed that studies on French loanwords from a phonological perspective have not received ample attention within either the framework of OT or another theory. The only adequate study is that of Benali (2018), who dealt with stress and intonation patterns of loanwords in Algerian Arabic. The findings show that speakers tend to transfer the stress and intonation pattern of Algerian Arabic to the French loanwords.…”
Section: Previous Studiesmentioning
confidence: 99%
“…As far as the Algerian context is concerned, reviewing the literature revealed that studies on French loanwords from a phonological perspective have not received ample attention within either the framework of OT or another theory. The only adequate study is that of Benali (2018), who dealt with stress and intonation patterns of loanwords in Algerian Arabic. The findings show that speakers tend to transfer the stress and intonation pattern of Algerian Arabic to the French loanwords.…”
Section: Previous Studiesmentioning
confidence: 99%